TiO2 and molecular sieve composite carrier supported Pt catalyst, preparation and application thereof in CO oxidation reaction

By using the preparation method of supporting Pt catalyst with a composite support of TiO2 and molecular sieve, the problem of inactivation of existing catalysts in the presence of SO2 is solved, and the higher CO catalytic oxidation activity and anti-sulfur poisoning properties are achieved, and it is suitable for complex flue gas treatment.

CN119500249AActive Publication Date: 2025-02-25HUAZHONG UNIV OF SCI & TECH +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411633384.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-25
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

The existing Pt/TiO2 catalysts are prone to inactivate in the presence of SO2, resulting in a decrease in CO oxidation reaction activity and making it difficult to effectively deal with complex flue gas components.

Method used

The preparation method of supporting Pt catalyst with TiO2 and molecular sieve composite support is adopted, and a catalyst with excellent CO catalytic oxidation performance and anti-sulfur poisoning ability is prepared through hydrothermal reaction and calcination steps.

Benefits of technology

The catalyst's CO catalytic oxidation activity and anti-sulfur poisoning properties are significantly improved. Compared with traditional Pt/TiO2 catalysts, the activity decreases less in the presence of SO2, and is suitable for CO catalytic oxidation treatment of mobile sources and fixed sources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500249A_ABST
    Figure CN119500249A_ABST
Patent Text Reader

Abstract

The invention relates to a TiO2 and molecular sieve composite carrier supported Pt catalyst, preparation and application thereof in CO oxidation reaction, and belongs to the technical field of industrial catalysis. The preparation process of the catalyst mainly comprises the following steps: preparing molecular sieve gel, adding TiO2 powder into the molecular sieve gel, fully mixing, and carrying out hydrothermal reaction to obtain the TiO2-molecular sieve composite material. And then carrying out high-temperature calcination on the obtained composite material to remove the template agent, and then carrying out ammonium exchange treatment to obtain the ammonium type TiO2-molecular sieve composite powder. And finally, fully mixing a Pt precursor solution with the composite carrier by adopting an impregnation method, and then drying and calcining at high temperature to prepare the Pt / TiO2-molecular sieve composite catalyst. The catalyst shows excellent activity and sulfur poisoning resistance in CO catalytic oxidation reaction, and is suitable for application scenarios such as mobile source and industrial tail gas treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of industrial catalysis, and more specifically to a Pt catalyst loaded on a TiO2 and molecular sieve composite carrier, and its preparation and application in CO oxidation reaction. Background Art

[0002] Carbon monoxide (CO) is a common air pollutant. Its main sources include incomplete combustion of fossil fuels, motor vehicle exhaust emissions, and waste gas emissions in industrial production, especially in energy-intensive industries. CO can cause serious harm to human health and the ecological environment, can hinder the normal oxygen delivery of the human body, and long-term exposure may lead to a series of health problems. Therefore, reducing CO emissions has become an urgent task for environmental governance. Catalytic oxidation technology has attracted widespread attention as an effective means of CO emission reduction. This technology efficiently converts CO into harmless carbon dioxide (CO2) through the action of catalysts, thereby achieving the purpose of purifying the air. The selection and design of catalysts are the key to this technology. Pt / TiO2 catalyst has become the focus of research due to its excellent CO catalytic oxidation performance. However, the flue gas composition in motor vehicle exhaust and industrial waste gas is relatively complex, among which SO2 can cause catalyst deactivation, which brings great challenges to the CO oxidation reaction. The deactivation of Pt / TiO2 catalyst is usually due to the fact that SO2 can be adsorbed and oxidized at the Pt site, and then transferred to the TiO2 carrier to form sulfate substances, blocking the catalyst pores and hindering the interaction between –OH and CO. Therefore, it is of great significance to improve the resistance of Pt / TiO2 catalyst to SO2 poisoning. Summary of the invention

[0003] In view of the limitations of the prior art, the present invention proposes a method for preparing a Pt catalyst supported on a TiO2 and molecular sieve composite carrier. The preparation method has a simple process, is easy to repeat, and has good consistency. The Pt / TiO2-molecular sieve catalyst prepared by this method exhibits excellent CO catalytic oxidation performance and excellent resistance to sulfur poisoning, and is suitable for CO catalytic oxidation treatment of mobile sources and fixed sources.

[0004] According to a first aspect of the present invention, there is provided a method for preparing a Pt catalyst supported on a TiO2 and molecular sieve composite carrier, comprising the following steps:

[0005] (1) dissolving an inorganic base in deionized water, adding an aluminum source, and mixing thoroughly; then adding a silicon source, and then adding a template agent to obtain a molecular sieve gel; adding TiO2 powder to the molecular sieve gel, and then performing a hydrothermal reaction;

[0006] (2) After the hydrothermal reaction is completed, the solid product is cooled and separated, washed with water to remove impurities and then dried; then calcined to remove the template to obtain a composite carrier of TiO2 and molecular sieve; the composite carrier of TiO2 and molecular sieve is ammonium exchanged to obtain an ammonium-type composite carrier of TiO2 and molecular sieve;

[0007] (3) Immersing the ammonium-type TiO2 and molecular sieve composite carrier obtained in step (2) into a platinum precursor solution, drying it, and then calcining it to obtain a TiO2 and molecular sieve composite carrier loaded with Pt catalyst.

[0008] Preferably, in step (1), the inorganic base is lithium hydroxide, sodium hydroxide or potassium hydroxide;

[0009] The aluminum source is sodium aluminate, aluminum nitrate, pseudo-boehmite or boehmite;

[0010] The silicon source is tetraethoxysilane, silica sol, ethyl orthosilicate or sodium silicate;

[0011] The template used is N,N,N-trimethyl-1-adamantyl ammonium hydroxide, N,N,N-trimethyl-1-adamantyl ammonium chloride, N,N-dimethyl-2,6-dimethylpiperidinium hydroxide, N,N-dimethyl-3,5-dimethylpiperidinium iodide, tetrapropylammonium hydroxide or tetrapropylammonium bromide.

[0012] Preferably, the molecular sieve gel is SSZ-13, SSZ-39 or BEA molecular sieve gel.

[0013] Preferably, in step (2), the calcination temperature is 400-700° C., and the ammonium salt used for the ammonium exchange is ammonium bicarbonate, ammonium bisulfate or ammonium acetate.

[0014] Preferably, in step (3), the calcination temperature is 400-700° C., and the platinum precursor is chloroplatinic acid, platinum nitrate or diammine dichloroplatinum;

[0015] The calcination atmosphere in step (3) is carbon monoxide, ammonia, nitrogen, oxygen or air.

[0016] According to another aspect of the present invention, a prepared TiO2 and molecular sieve composite carrier-loaded Pt catalyst is provided.

[0017] Preferably, the loading amount of the active component Pt in the Pt catalyst loaded on the TiO2 and molecular sieve composite carrier is 0.4wt.% to 4wt.%, and the mass ratio of TiO2 to molecular sieve in the carrier is 0.5 to 5.

[0018] According to another aspect of the present invention, there is provided the use of the TiO2 and molecular sieve composite carrier-supported Pt catalyst in CO catalytic oxidation reaction.

[0019] According to another aspect of the present invention, a CO catalytic oxidizer is provided, comprising the Pt catalyst loaded on the TiO2 and molecular sieve composite carrier.

[0020] According to another aspect of the present invention, there is provided a system for treating tail gas from a mobile source or a fixed source, comprising the CO catalytic oxidizer.

[0021] In general, the above technical solution conceived by the present invention has the following technical advantages compared with the prior art:

[0022] (1) The present invention proposes a method for preparing a Pt / TiO2-molecular sieve catalyst, which is simple to operate, easy to repeat, and has good controllability and consistency, and is intended to optimize the CO catalytic oxidation performance. 90 Compared with the catalysts Pt / TiO2-SSZ-13, Pt / TiO2-SSZ-39 and Pt / TiO2-BEA provided by the present invention, the T 90 After SO2 was introduced into the reaction atmosphere, the T 90 They increased to 269°C, 227°C, 218°C and 239°C respectively, indicating that the CO catalytic oxidation activity of all catalysts decreased in the presence of SO2. Then, the activity of the Pt / TiO2 catalyst decreased most significantly. In contrast, the decrease in CO catalytic oxidation performance of the Pt / TiO2-SSZ-13, Pt / TiO2-SSZ-39 and Pt / TiO2-BEA catalysts was relatively small, showing better resistance to sulfur poisoning. This shows that the TiO2-molecular sieve composite carrier can significantly improve the CO catalytic oxidation activity and sulfur resistance of the Pt / TiO2 catalyst. The Pt / TiO2-molecular sieve catalyst of the present invention is particularly suitable for tail gas purification treatment of mobile sources and fixed sources due to its higher CO oxidation activity and resistance to sulfur poisoning, providing a more advantageous solution for practical applications.

[0023] (2) Using molecular sieves and TiO2 as carriers to load Pt can make the dispersion of Pt nanoparticles in the molecular sieve more uniform, thereby reducing the agglomeration of Pt particles and improving the activity of the catalyst. This is because the molecular sieve has rich micropores and mesoporous structures. This highly ordered pore system can increase the specific surface area of ​​the catalyst and provide more exposed active sites. In addition, the molecular sieve contains more acidic sites that can promote the adsorption and activation process of CO, which helps to improve the CO conversion rate of the catalyst. TiO2 itself is an excellent oxidation carrier that can provide lattice oxygen in the CO catalytic oxidation reaction. However, the composite of molecular sieves and TiO2 further enhances the redox performance of the carrier and improves the migration and supply of oxygen. The special environment in the molecular sieve pores can further promote the activation and transfer of oxygen, making it easier for reactive oxygen species to generate and participate in the reaction, thereby improving the overall CO catalytic oxidation efficiency of the catalyst. In terms of anti-sulfur poisoning performance, the composite carrier of TiO2 and molecular sieves can effectively limit the combination of SO2 and Pt due to its more acidic sites and unique pore structure. In addition, the acidic sites of the molecular sieve can interact with SO2, weakening the interaction between SO2 and Pt particles, thereby alleviating the sulfur poisoning of the catalyst. More importantly, the TiO2 and molecular sieve composite carrier can form a special interface structure, enhance the electron transfer between Pt and the carrier, optimize the electronic state of Pt, and thus improve its sulfur resistance. These mechanisms work together to make the modified catalyst show better catalytic performance and stability in complex atmospheres, suitable for a wide range of practical applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 X-ray diffraction (XRD) patterns of Pt / TiO2-SSZ-13, Pt / TiO2-SSZ-39, Pt / TiO2-BEA and Pt / TiO2 catalysts prepared in Examples 1 to 3 and Comparative Example 1.

[0025] Figure 2 This is a graph showing the CO catalytic oxidation conversion rates of Pt / TiO2-SSZ-13, Pt / TiO2-SSZ-39, Pt / TiO2-BEA and Pt / TiO2 catalysts prepared in Examples 1 to 3 and Comparative Example 1.

[0026] Figure 3 This is a graph showing the CO catalytic oxidation conversion rate of Pt / TiO2-SSZ-13, Pt / TiO2-SSZ-39, Pt / TiO2-BEA and Pt / TiO2 catalysts prepared in Examples 1 to 3 and Comparative Example 1 in the presence of 200 ppm SO2. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0028] In a first aspect of the present invention, a method for preparing a Pt catalyst supported on a TiO2 and molecular sieve composite carrier is provided, comprising the following steps:

[0029] (1) Dissolve the titanium source in an appropriate amount of anhydrous ethanol or isopropanol, and stir at 30-80°C for 0.5-3 hours to fully dissolve it. During the stirring process, add an appropriate amount of deionized water dropwise to control the reaction temperature and the water addition rate. The entire water addition process should last for 1-3 hours to ensure slow hydrolysis. After the hydrolysis is completed, the resulting sol is allowed to stand for 6-24 hours to promote aging and form a stable TiO2 sol. Dry the TiO2 sol at 70-100°C for 12 hours to obtain TiO2 powder.

[0030] (2) Dissolve the inorganic base in deionized water and stir at room temperature for 2 to 15 minutes. Subsequently, add the aluminum source and continue stirring for 5 to 30 minutes to ensure that the aluminum source is evenly dispersed in the solution. Next, slowly add the silicon source and stir for 1 to 3 hours. Subsequently, add the template and continue stirring for 0.5 to 3 hours to obtain a molecular sieve gel. On this basis, slowly add the prefabricated TiO2 powder to the molecular sieve gel and stir for 0.5 to 4 hours to ensure that the composite material is fully mixed. Finally, place the evenly mixed TiO2-molecular sieve gel in a hydrothermal reactor and perform a hydrothermal reaction at 120 to 200°C for 1 to 7 days.

[0031] (3) After the hydrothermal reaction is completed, the solid product is cooled and separated, and impurities are removed by multiple water washing. The washed product is dried at 70-100°C for 12 hours, and then calcined at 400-700°C for 2-8 hours to remove the template and other organic residues, and finally a TiO2-molecular sieve composite material is obtained. The obtained TiO2-molecular sieve composite powder is ammonium exchanged with ammonium bicarbonate, ammonium bisulfate or ammonium acetate to obtain an ammonium-type TiO2-molecular sieve composite powder.

[0032] (4) Dissolve the Pt salt in distilled water and stir at 30-80°C for 0.5-2 hours, immerse the ammonium TiO2-molecular sieve composite carrier into the platinum precursor solution, and stir for 1-5 hours to ensure that the Pt precursor is fully adsorbed on the carrier. Then dry the mixed slurry at 70-100°C for 12 hours, and calcine at 400-700°C in a special atmosphere for 2-8 hours to finally obtain a Pt / TiO2-molecular sieve composite carrier catalyst.

[0033] Preferably, the titanium source in step (1) is tetrabutyl titanate, isopropyl titanate, tetraethyl titanate or titanium tetrachloride.

[0034] Preferably, the inorganic base in step (2) is lithium hydroxide, sodium hydroxide or potassium hydroxide. The aluminum source is sodium aluminate, aluminum nitrate, USY molecular sieve, BEA molecular sieve, pseudo-boehmite or boehmite. The silicon source is tetraethoxysilane, silica sol, ethyl orthosilicate or sodium silicate. The template used is N, N, N-trimethyl-1-adamantyl ammonium hydroxide, N, N, N-trimethyl-1-adamantyl ammonium chloride, N, N-dimethyl-2,6-dimethylpiperidinium hydroxide, N, N-dimethyl-3,5-dimethylpiperidinium iodide, tetrapropylammonium hydroxide or tetrapropylammonium bromide. The molecular sieve gel is SSZ-13, SSZ-39 or BEA molecular sieve gel.

[0035] Preferably, the calcination temperature in step (3) is 400-700° C., and the ammonium salt used for the ammonium exchange is ammonium bicarbonate, ammonium bisulfate or ammonium acetate.

[0036] Preferably, the Pt salt in step (4) is chloroplatinic acid, platinum nitrate or diammine dichloroplatinum. The calcination temperature is 400-700° C., and the special atmosphere is carbon monoxide, ammonia, nitrogen, oxygen or air.

[0037] In some embodiments, the titanium source used in step (1) is tetrabutyl titanate, isopropyl titanate, tetraethyl titanate or titanium tetrachloride.

[0038] In some embodiments, the inorganic base used in step (2) is lithium hydroxide, sodium hydroxide or potassium hydroxide. The aluminum source used is sodium aluminate, aluminum nitrate, USY molecular sieve, BEA molecular sieve, pseudo-boehmite or boehmite. The silicon source used is tetraethoxysilane, silica sol, ethyl orthosilicate or sodium silicate. The template used is N, N, N-trimethyl-1-adamantyl ammonium hydroxide, N, N, N-trimethyl-1-adamantyl ammonium chloride, N, N-dimethyl-2,6-dimethylpiperidinium hydroxide, N, N-dimethyl-3,5-dimethylpiperidinium iodide, tetrapropylammonium hydroxide or tetrapropylammonium bromide. The obtained molecular sieve gel is SSZ-13, SSZ-39 or BEA molecular sieve gel.

[0039] In some embodiments, the calcination temperature used in step (3) is 400-700° C., and the ammonium salt used for ammonium exchange is ammonium bicarbonate, ammonium bisulfate or ammonium acetate.

[0040] In some embodiments, the Pt salt used in step (4) is chloroplatinic acid, platinum nitrate or diammine dichloroplatinum. The calcination temperature is 400-700° C., and the calcination atmosphere is carbon monoxide, ammonia, nitrogen, oxygen or air.

[0041] In a second aspect, the present invention provides a Pt / TiO2-molecular sieve catalyst for CO catalytic oxidation, comprising an active component and a carrier; the active component is a Pt species, and the carrier is a composite of TiO2 and SSZ-13, SSZ-39 or BEA molecular sieves.

[0042] In some embodiments, the loading amount of the active component Pt in the carrier is 0.4 wt.% to 4 wt.%, more preferably 0.8 wt.%. The mass ratio of TiO2 to molecular sieve in the carrier is 0.5 to 5, more preferably 2.

[0043] In a third aspect, the present invention provides a CO catalytic oxidizer comprising the above-mentioned Pt / TiO2-molecular sieve catalyst.

[0044] According to a fourth aspect of the present invention, there is provided a mobile source and a fixed source exhaust gas treatment system comprising the above-mentioned CO catalytic oxidizer.

[0045] The following are specific embodiments

[0046] Example 1

[0047] A method for preparing a Pt / TiO2-SSZ-13 catalyst comprises the following steps:

[0048] (1) Dissolve 16.86 g of tetrabutyl titanate in 50 mL of anhydrous ethanol and stir at 50 ° C for 2 hours to fully dissolve it. During the stirring process, add 50 mL of deionized water dropwise, keep the reaction temperature at 50 ° C and control the water addition rate. The entire water addition process lasts for 2 hours to ensure slow hydrolysis. After the hydrolysis is completed, the resulting sol is allowed to stand for 10 hours to promote aging and form a stable TiO2 sol. The TiO2 sol is dried at 80 ° C for 12 hours to obtain TiO2 powder.

[0049] (2) Dissolve 0.5g of sodium hydroxide in deionized water and stir at room temperature for 5 minutes. Subsequently, add 1g of aluminum nitrate and continue stirring for 15 minutes. Next, slowly add 6g of silica sol and stir for 2 hours. Subsequently, add 5g of N,N,N-trimethyl-1-adamantyl ammonium chloride and continue stirring for 1 hour to obtain SSZ-13 molecular sieve gel. On this basis, slowly add the prefabricated TiO2 powder into the SSZ-13 gel and stir for 2 hours to ensure that the composite material is fully mixed. Finally, place the evenly mixed TiO2-SSZ-13 gel in a hydrothermal reactor and perform hydrothermal reaction at 140°C for 6 days.

[0050] (3) After the hydrothermal reaction is completed, the solid product is cooled and separated, and impurities are removed by multiple water washing. The washed product is dried at 80°C for 12 hours, and then calcined at 500°C for 4 hours to remove the template and other organic residues, and finally a TiO2-SSZ-13 composite material is obtained. The obtained TiO2-SSZ-13 composite powder is ammonium exchanged with 1M ammonium bicarbonate to obtain an ammonium-type TiO2-SSZ-13 composite powder.

[0051] (4) 0.12 g of chloroplatinic acid was dissolved in distilled water and stirred at 60°C for 1 hour. The ammonium-type TiO2-SSZ-13 composite carrier was immersed in the chloroplatinic acid solution and stirred for 5 hours to ensure that the Pt precursor was fully adsorbed on the carrier. The mixed slurry was then dried at 70°C for 12 hours and calcined at 500°C in a CO atmosphere for 4 hours to finally obtain a Pt / TiO2-SSZ-13 composite carrier catalyst with a Pt content of 0.8 wt.%.

[0052] Comparative Example 1

[0053] A method for preparing a Pt / TiO2 catalyst comprises the following steps:

[0054] (1) Dissolve 25.29 g of tetrabutyl titanate in 50 mL of anhydrous ethanol and stir at 50 ° C for 2 hours to fully dissolve it. During the stirring process, add 50 mL of deionized water dropwise, keep the reaction temperature at 50 ° C and control the water addition rate. The entire water addition process lasts for 2 hours to ensure slow hydrolysis. After the hydrolysis is completed, the resulting sol is allowed to stand for 10 hours to promote aging and form a stable TiO2 sol. The TiO2 sol is dried at 80 ° C for 12 hours to obtain TiO2 powder. The obtained TiO2 powder is ammonium exchanged with 1M ammonium bicarbonate to obtain ammonium-type TiO2 powder.

[0055] (2) 0.12 g of chloroplatinic acid was dissolved in distilled water and stirred at 60°C for 1 hour. The ammonium-type TiO2 carrier was immersed in the chloroplatinic acid solution and stirred for 5 hours to ensure that the Pt precursor was fully adsorbed on the carrier. The mixed slurry was then dried at 70°C for 12 hours and calcined at 500°C in a CO atmosphere for 4 hours to finally obtain a Pt / TiO2 catalyst with a Pt content of 0.8 wt.%.

[0056] Example 2

[0057] A method for preparing a Pt / TiO2-SSZ-39 catalyst comprises the following steps:

[0058] (1) Dissolve 14.09 g of isopropyl titanate in 50 mL of anhydrous ethanol and stir at 60 ° C for 1.5 hours to fully dissolve it. During the stirring process, add 50 mL of deionized water dropwise, keep the reaction temperature at 60 ° C and control the water addition rate. The entire water addition process lasts for 2 hours to ensure slow hydrolysis. After the hydrolysis is completed, the resulting sol is allowed to stand for 12 hours to promote aging and form a stable TiO2 sol. The TiO2 sol is dried at 90 ° C for 12 hours to obtain TiO2 powder.

[0059] (2) Dissolve 0.8g lithium hydroxide in deionized water and stir at room temperature for 6 minutes. Subsequently, add 2g BEA molecular sieve and continue stirring for 30 minutes. Next, slowly add 6.5g sodium silicate and stir for 2 hours. Subsequently, add 6g N,N-dimethyl-2,6-dimethylpiperidinium hydroxide and continue stirring for 1.5 hours to obtain SSZ-39 molecular sieve gel. On this basis, slowly add the prefabricated TiO2 powder into the SSZ-39 gel and stir for 2.5 hours to ensure that the composite material is fully mixed. Finally, place the evenly mixed TiO2-SSZ-39 gel in a hydrothermal reactor and perform hydrothermal reaction at 200°C for 2 days.

[0060] (3) After the hydrothermal reaction is completed, the solid product is cooled and separated, and impurities are removed by multiple water washing. The washed product is dried at 90°C for 12 hours, and then calcined at 550°C for 3 hours to remove the template and other organic residues, and finally a TiO2-SSZ-39 composite material is obtained. The obtained TiO2-SSZ-39 composite powder is ammonium exchanged with 1M ammonium bisulfate to obtain an ammonium-type TiO2-SSZ-39 composite powder.

[0061] (4) 0.12 g of chloroplatinic acid was dissolved in distilled water and stirred at 70°C for 1 hour. The ammonium-type TiO2-SSZ-39 composite carrier was immersed in the chloroplatinic acid solution and stirred for 4 hours to ensure that the Pt precursor was fully adsorbed on the carrier. The mixed slurry was then dried at 90°C for 12 hours and calcined at 550°C in an ammonia atmosphere for 3 hours to finally obtain a Pt / TiO2-SSZ-39 composite carrier catalyst with a Pt content of 0.8 wt.%.

[0062] Example 3

[0063] A method for preparing a Pt / TiO2-BEA catalyst comprises the following steps:

[0064] (1) Dissolve 12.31 g of tetraethyl titanate in 60 mL of isopropanol and stir at 70°C for 1.5 hours to fully dissolve it. During the stirring process, add 60 mL of deionized water dropwise, keep the reaction temperature at 70°C and control the water addition rate. The entire water addition process lasts for 1 hour to ensure slow hydrolysis. After the hydrolysis is completed, the resulting sol is allowed to stand for 20 hours to promote aging and form a stable TiO2 sol. The TiO2 sol is dried at 100°C for 12 hours to obtain TiO2 powder.

[0065] (2) Dissolve 1.4 g of potassium hydroxide in deionized water and stir at room temperature for 15 minutes. Subsequently, add 8 g of boehmite and continue stirring for 25 minutes. Next, slowly add 8 g of tetraethoxysilane and stir for 2 hours. Subsequently, add 10 g of tetrapropylammonium bromide and continue stirring for 1.5 hours to obtain BEA molecular sieve gel. On this basis, slowly add the prefabricated TiO2 powder into the BEA molecular sieve gel and stir for 3 hours to ensure that the composite material is fully mixed. Finally, place the evenly mixed TiO2-BEA gel in a hydrothermal reactor and carry out hydrothermal reaction at 120°C for 5 days.

[0066] (3) After the hydrothermal reaction is completed, the solid product is cooled and separated, and impurities are removed by multiple water washing. The washed product is dried at 80°C for 12 hours, and then calcined at 600°C for 5 hours to remove the template and other organic residues, and finally a TiO2-BEA composite material is obtained. The obtained TiO2-BEA composite powder is ammonium exchanged with 1M ammonium acetate to obtain an ammonium-type TiO2-BEA composite powder.

[0067] (4) 0.20 g of platinum nitrate was dissolved in distilled water and stirred at 50° C. for 2 hours, and the ammonium-type TiO2-BEA composite carrier was immersed in the platinum nitrate solution and stirred for 3 hours to ensure that the Pt precursor was fully adsorbed on the carrier. The mixed slurry was then dried at 80° C. for 12 hours and calcined at 600° C. for 5 hours in a nitrogen atmosphere to finally obtain a Pt / TiO2-BEA composite carrier catalyst with a Pt content of 1.0 wt.%.

[0068] XRD tests were performed on Pt / TiO2-SSZ-13, Pt / TiO2-SSZ-39, Pt / TiO2-BEA and Pt / TiO2 catalysts prepared in Examples 1 to 3 and Comparative Example 1. The results are as follows: Figure 1As shown, Pt / TiO2-SSZ-13 has the characteristic structure of typical anatase TiO2 and CHA molecular sieve; Pt / TiO2-SSZ-39 shows the typical structure of anatase TiO2 and AEI molecular sieve; and Pt / TiO2-BEA shows the typical structural characteristics of anatase TiO2 and BEA molecular sieve. Pt / TiO2 has the diffraction peak of anatase TiO2.

[0069] Embodiments 4 to 7

[0070] The preparation method of Pt / TiO2-SSZ-39 catalyst with different Pt loading amounts comprises the following steps:

[0071] (1) 13.47 g of tetraethyl titanate was dissolved in 60 mL of isopropanol and stirred at 80°C for 3 hours to fully dissolve it. During the stirring process, 60 mL of deionized water was added dropwise, the reaction temperature was maintained at 80°C and the water addition rate was controlled. The entire water addition process lasted for 3 hours to ensure slow hydrolysis. After the hydrolysis was completed, the resulting sol was allowed to stand for 20 hours to promote aging and form a stable TiO2 sol. The TiO2 sol was dried at 100°C for 12 hours to obtain TiO2 powder.

[0072] (2) Dissolve 1.0 g of sodium hydroxide in deionized water and stir at room temperature for 15 minutes. Subsequently, add 3 g of USY molecular sieve and continue stirring for 30 minutes. Next, slowly add 8 g of ethyl orthosilicate and stir for 3 hours. Subsequently, add 12 g of N,N-dimethyl-3,5-dimethylpiperidinium iodide and continue stirring for another 3 hours to obtain SSZ-39 molecular sieve gel. On this basis, slowly add the prefabricated TiO2 powder to the SSZ-39 gel and stir for 4 hours to ensure that the composite material is fully mixed. Finally, place the evenly mixed TiO2-SSZ-39 gel in a hydrothermal reactor and perform a hydrothermal reaction at 190°C for 3 days.

[0073] (3) After the hydrothermal reaction is completed, the solid product is cooled and separated, and impurities are removed by multiple water washing. The washed product is dried at 100°C for 12 hours, and then calcined at 700°C for 5 hours to remove the template and other organic residues, and finally a TiO2-SSZ-39 composite material is obtained. The obtained TiO2-SSZ-39 composite powder is ammonium exchanged with 1M ammonium acetate to obtain an ammonium-type TiO2-SSZ-39 composite powder.

[0074] (4) 0.045g, 0.09g, 0.135g or 0.179g of dichlorodiammine platinum was dissolved in distilled water and stirred at 80°C for 2 hours, and the ammonium type TiO2-SSZ-39 composite carrier was immersed in the dichlorodiammine platinum solution and stirred for 5 hours to ensure that the Pt precursor was fully adsorbed on the carrier. The mixed slurry was then dried at 100°C for 12 hours and calcined at 700°C in an air atmosphere for 5 hours to finally obtain a Pt / TiO2-SSZ-39 composite carrier catalyst with a Pt content of 0.5wt.%, 1.0wt.%, 1.5wt.% and 2.0wt.%.

[0075] Embodiments 8 to 11

[0076] The preparation method of Pt / TiO2-SSZ-13 catalyst with different mass ratios of TiO2 and SSZ-13 molecular sieve comprises the following steps:

[0077] (1) 16.86 g, 25.3 g, 30.35 g or 33.73 g of tetraethyl titanate was dissolved in 70 mL of anhydrous ethanol and stirred at 40 ° C for 1 hour to fully dissolve it. During the stirring process, 70 mL of deionized water was added dropwise, the reaction temperature was maintained at 40 ° C and the water addition rate was controlled. The entire water addition process lasted for 1 hour to ensure slow hydrolysis. After the hydrolysis was completed, the obtained sol was allowed to stand for 6 hours to promote aging and form a stable TiO2 sol. The TiO2 sol was dried at 70 ° C for 12 hours to obtain TiO2 powder.

[0078] (2) Dissolve 1.5 g of sodium hydroxide in deionized water and stir at room temperature for 3 minutes. Subsequently, add 0.5 g of sodium aluminate and continue stirring for 5 minutes. Next, slowly add 15 g of tetraethoxysilane and stir for 1 hour. Subsequently, add 10 g of N,N,N-trimethyl-1-adamantyl ammonium hydroxide and continue stirring for 1.5 hours to obtain SSZ-13 molecular sieve gel. On this basis, slowly add the prefabricated TiO2 powder to the SSZ-13 gel and stir for 1 hour to ensure that the composite material is fully mixed. Finally, place the evenly mixed TiO2-SSZ-13 gel in a hydrothermal reactor and perform a hydrothermal reaction at 170°C for 3 days.

[0079] (3) After the hydrothermal reaction is completed, the solid product is cooled and separated, and impurities are removed by multiple water washing. The washed product is dried at 70°C for 12 hours, and then calcined at 400°C for 6 hours to remove the template and other organic residues, and finally a TiO2-SSZ-13 composite material is obtained. The obtained TiO2-SSZ-13 composite powder is ammonium exchanged with 1M ammonium bisulfate to obtain an ammonium-type TiO2-SSZ-13 composite powder.

[0080] (4) 0.24 g of platinum nitrate was dissolved in distilled water and stirred at 40° C. for 1 hour, and the ammonium-type TiO2-SSZ-13 composite carrier was immersed in the platinum nitrate solution and stirred for 3 hours to ensure that the Pt precursor was fully adsorbed on the carrier. The mixed slurry was then dried at 70° C. for 12 hours and calcined at 400° C. in an oxygen atmosphere for 6 hours to finally obtain a Pt / TiO2-SSZ-13 composite carrier catalyst with a mass ratio of TiO2 to SSZ-13 molecular sieve of 0.5, 1, 1.5 or 2 and a Pt content of 1.2 wt.%.

[0081] Embodiments 12 to 15

[0082] The preparation method of Pt / TiO2-BEA catalyst prepared from different titanium sources comprises the following steps:

[0083] (1) Dissolve 17.54 g of tetraethyl titanate, 14.65 g of isopropyl titanate, 11.75 g of tetraethyl titanate or 9.77 g of titanium tetrachloride in 80 mL of isopropanol and stir at 60 ° C for 2 hours to fully dissolve it. During the stirring process, add 80 mL of deionized water dropwise, keep the reaction temperature at 60 ° C and control the water addition rate. The entire water addition process lasts for 2 hours to ensure slow hydrolysis. After the hydrolysis is completed, the resulting sol is allowed to stand for 20 hours to promote aging and form a stable TiO2 sol. The TiO2 sol is dried at 90 ° C for 12 hours to obtain TiO2 powder.

[0084] (2) Dissolve 1.7 g of sodium hydroxide in deionized water and stir at room temperature for 7 minutes. Subsequently, add 7 g of pseudo-boehmite and continue stirring for 12 minutes. Next, slowly add 10 g of silica sol and stir for 2 hours. Subsequently, add 17 g of tetrapropylammonium hydroxide and continue stirring for 2.5 hours to obtain BEA molecular sieve gel. On this basis, slowly add the prefabricated TiO2 powder into the BEA molecular sieve gel and stir for 3.5 hours to ensure that the composite material is fully mixed. Finally, place the evenly mixed TiO2-BEA gel in a hydrothermal reactor and perform a hydrothermal reaction at 160°C for 4 days.

[0085] (3) After the hydrothermal reaction is completed, the solid product is cooled and separated, and impurities are removed by multiple water washing. The washed product is dried at 80°C for 12 hours, and then calcined at 650°C for 4 hours to remove the template and other organic residues, and finally a TiO2-BEA composite material is obtained. The obtained TiO2-BEA composite powder is ammonium exchanged with 1M ammonium hydrogen sulfate to obtain an ammonium-type TiO2-BEA composite powder.

[0086] (4) 0.21 g of diammine dichloroplatinum was dissolved in distilled water and stirred at 30° C. for 2 hours. The ammonium-type TiO2-BEA composite carrier was immersed in the diammine dichloroplatinum solution and stirred for 3 hours to ensure that the Pt precursor was fully adsorbed on the carrier. The mixed slurry was then dried at 80° C. for 12 hours and calcined at 650° C. for 4 hours in a carbon monoxide atmosphere to finally obtain a Pt / TiO2-BEA composite carrier catalyst with a Pt content of 2.0 wt.%.

[0087] Example 16

[0088] The CO catalytic oxidation performance and sulfur resistance performance of Pt / TiO2-SSZ-13, Pt / TiO2-SSZ-39, Pt / TiO2-BEA and Pt / TiO2 catalysts prepared in Examples 1 to 3 and Comparative Example 1 were tested. The test conditions were: catalyst dosage 0.2g (60-80 mesh), simulated flue gas composition of 1000ppm CO, 15% H2O, 10% O2, 200ppm SO2 (introduced when necessary), reaction space velocity of 150000h -1 .

[0089] The results of CO catalytic oxidation performance test and sulfur resistance test are as follows Figure 2 and Figure 3 As shown. Figure 2 It can be seen that compared with Pt / TiO2 catalyst, Pt / TiO2-molecular sieve catalyst has higher CO catalytic oxidation performance. This is because the molecular sieve has rich micropores and mesoporous structures. This highly ordered pore system can increase the specific surface area of ​​the catalyst, making the dispersion of Pt nanoparticles in the molecular sieve more uniform, thereby reducing the agglomeration of Pt particles and improving the activity of the catalyst. In addition, the molecular sieve contains more acidic sites to promote the adsorption and activation process of CO. The composite of molecular sieve and TiO2 further enhances the redox performance of the carrier and improves the migration and supply of oxygen, which helps to improve the CO conversion rate of the catalyst. After SO2 was introduced into the reaction atmosphere, the CO catalytic oxidation activity of all catalysts decreased. Then, the activity of Pt / TiO2 catalyst decreased most significantly. In contrast, the decrease in CO catalytic oxidation performance of Pt / TiO2-SSZ-13, Pt / TiO2-SSZ-39 and Pt / TiO2-BEA catalysts was relatively small, showing better anti-sulfur poisoning performance. This is because the composite carrier of TiO2 and molecular sieve has more acidic sites and unique pore structure, which can effectively limit the combination of SO2 and Pt, reduce the deposition of sulfur species on the catalyst surface and the poisoning of active sites. Molecular sieve can also be used as a sacrificial site to adsorb SO2, to a certain extent protecting active species from being poisoned by sulfur, thereby improving the catalyst's anti-sulfur poisoning performance.

[0090] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a Pt catalyst supported on a TiO2 and molecular sieve composite carrier, characterized in that: The following steps are involved: (1) dissolving an inorganic base in deionized water, adding an aluminum source, and mixing thoroughly; then adding a silicon source, and then adding a template agent to obtain a molecular sieve gel; adding TiO2 powder to the molecular sieve gel, and then performing a hydrothermal reaction; (2) After the hydrothermal reaction is completed, the solid product is cooled and separated, washed with water to remove impurities and then dried; then calcined to remove the template to obtain a composite carrier of TiO2 and molecular sieve; the composite carrier of TiO2 and molecular sieve is ammonium exchanged to obtain an ammonium-type composite carrier of TiO2 and molecular sieve; (3) Immersing the ammonium-type TiO2 and molecular sieve composite carrier obtained in step (2) into a platinum precursor solution, drying it, and then calcining it to obtain a TiO2 and molecular sieve composite carrier loaded with Pt catalyst.

2. The method for preparing a Pt catalyst supported on a TiO2 and molecular sieve composite carrier according to claim 1, characterized in that: In step (1), the inorganic base is lithium hydroxide, sodium hydroxide or potassium hydroxide; The aluminum source is sodium aluminate, aluminum nitrate, pseudo-boehmite or boehmite; The silicon source is tetraethoxysilane, silica sol, ethyl orthosilicate or sodium silicate; The template used is N,N,N-trimethyl-1-adamantyl ammonium hydroxide, N,N,N-trimethyl-1-adamantyl ammonium chloride, N,N-dimethyl-2,6-dimethylpiperidinium hydroxide, N,N-dimethyl-3,5-dimethylpiperidinium iodide, tetrapropylammonium hydroxide or tetrapropylammonium bromide.

3. The method for preparing a Pt catalyst supported on a TiO2 and molecular sieve composite carrier according to claim 1, characterized in that: The molecular sieve gel is SSZ-13, SSZ-39 or BEA molecular sieve gel.

4. The method for preparing a Pt catalyst supported on a TiO2 and molecular sieve composite carrier according to claim 1, characterized in that: In step (2), the calcination temperature is 400-700° C., and the ammonium salt used for the ammonium exchange is ammonium bicarbonate, ammonium bisulfate or ammonium acetate.

5. The method for preparing a Pt catalyst supported on a TiO2 and molecular sieve composite carrier according to claim 1, characterized in that: In step (3), the calcination temperature is 400-700° C., and the platinum precursor is chloroplatinic acid, platinum nitrate or diammine dichloroplatinum; The calcination atmosphere in step (3) is carbon monoxide, ammonia, nitrogen, oxygen or air.

6. A Pt catalyst loaded on a composite carrier of TiO2 and molecular sieve prepared according to any one of claims 1 to 5.

7. The Pt catalyst supported on a composite carrier of TiO2 and molecular sieve as claimed in claim 6, characterized in that: The loading amount of the active component Pt in the Pt catalyst loaded with the composite carrier of TiO2 and molecular sieve is 0.4wt.% to 4wt.%, and the mass ratio of TiO2 to molecular sieve in the carrier is 0.5 to 5.

8. Use of the TiO2 and molecular sieve composite carrier-supported Pt catalyst as claimed in claim 6 or 7 in CO catalytic oxidation reaction.

9. A CO catalytic oxidizer, characterized in that: It comprises the TiO2 and molecular sieve composite carrier loaded Pt catalyst as described in claim 6 or 7.

10. A system for treating tail gas from a mobile source or a fixed source, characterized in that: Comprising the CO catalytic oxidizer as described in claim 9.

Citation Information

Patent Citations

  • Preparation method of nano CuO / TiO2 / Fe modified zeolite composite photocatalyst

    CN106179460A

  • Method of synthesizing SSZ-39 molecular sieve through one-step process

    CN106467306A

  • Preparation method and application of Pt-coated AEI catalyst with packaging structure

    CN117531536A

  • Molecular sieve catalyst as well as preparation method and application thereof

    CN117696109A

  • Catalyst comprising an AFX-structure zeolite of very high purity and at least one transition metal for selective reduction of no x

    WO2019224086A1